Quality metrics of an integrated e-learning system – students’ perspective - Klasnić, Ksenija, sociologinja (Array, 2010)
As e-learning has become an increasingly important issue in educational systems in the last several years, a considerable number of generic standards, quality guidelines and frameworks have been published relating to better efficiency and quality improvement of the e-learning. While early initiatives were concentrated on the functional understanding and technical skills of ICT use, nowadays they take more into consideration motivation, satisfaction and contextualization which are reflected in the quality of e-learning. In the first part of the paper, different views towards the quality of an integrated e-learning system have been considered. In the second part, the research results regarding the quality of the integrated e-learning system (Moodle) have been presented and discussed in relation to different European policies. The survey was made on the Croatian version of Moodle (Omega) at the Faculty of Humanities and Social Sciences, University of Zagreb.